Dynamic profile of ocular refraction in pediatric cataract patients after lens surgeries - Liu, Zhen-Zhen (Int J Ophthalmol, 2019)
AIM: To study the change in ocular refraction in patients with pediatric cataracts (PCs) after lens extraction. METHODS: A total of 1258 patients who were undergoing cataract extraction with/without intraocular lens (IOL) implantation were recruited during preoperative examinations between Jan 2010 and Oct 2013. Patient ages ranged from 1.5mo to 14y. Follow-ups were conducted at 1wk, 1, and 3mo postoperatively and every 3mo in the first year, then 6mo thereafter. Ocular refraction [evaluated as spherical equivalent (SE)] and yearly myopic shift (YMS) were recorded and statistically analyzed among patients with age at surgery, baseline ocular refraction, gender, postoperative time and laterality (bilateral vs unilateral). RESULTS: By Dec 31(st) 2015, 1172 participants had been followed for more than 2y. The median follow-up period was 3y. The critical factors affecting the ocular refraction of PC patients were baseline ocular refraction, postoperative time for both aphakic and pseudophakic eyes. YMS grew most rapidly in young childhood and early adolescence. CONCLUSION: After lens surgeries, ocular refraction in PC patients shows an individual difference of change. Further concerns should be raising to monitor the rapid myopic shift at early adolescence of these patients.